Of fools and men: Iurodstvo in fifteenth- and sixteenth-century Russia - Vaz Pinto Simões Coelho, S (2024)
This thesis investigates the emergence and rise in popularity of a type of saint known in Russian as iurodivyi, and in English as holy fool or fool for Christ, in late fifteenth- and sixteenth-century Russia. In doing so, it breaks with past scholarship on the topic, which has often depicted iurodstvo as a monolithic phenomenon shrouded in myth, and contributes to the scholarly understanding of the pre-modern cult of saints, while offering a fresh perspective on a period of Russian history often labelled ‘of state formation’.